Perceptions of coffee producers concerning the impact of COVID-19 in Los Santos, Costa Rica - Díaz Porras, Rafael (2023)
The health crisis caused by the COVID-19 pandemic has resulted in significant and prolonged challenges to countries worldwide.  In Costa Rica, almost all sectors have been affected in some way. Alterations in basic living conditions, social and labor relations, business practices, and aspects of agricultural production have been especially challenged. This study evaluates the attitudes of coffee farmers towards the rapidly changing conditions imposed by the pandemic on farming operations, immigration policies, and local, regional, and international market fluctuations.  Growers were administered a survey that addresses concerns about coffee production and their fears about future developments within the industry.  A total of 119 producers were interviewed in the Los Santos region of Dota, Tarrazú, and León Cortes during the months of September and October of 2020, just before the harvest season.  This region was selected because of its importance in producing some of the highest quality coffee in the country. A 34-question survey employing a five-option Likert scale was used to determine whether producers agreed or disagreed with questions that addressed a variety of topics related to the pandemic and its influence on their collective operations and marketing concerns.  Results indicate that the main concerns of coffee growers centered around the increase in production costs, variability in coffee markets, and the potential loss of production owing to labor shortages during the harvest season.